Соціально-економічна ефективність використання рекреаційних ресурсів у форматі сталого розвитку - Ілляшенко, І.О.; Яблонська, В.І. (Економіка природокористування і охорони довкілля, 2013)
Визначено принципи та особливості оцінки ефективності використання рекреаційних ресурсів в умовах концепції сталого розвитку. Наведено детермінанти соціального ефекту їх застосування. The features of assessing the effectiveness of recreation resources in terms of sustainable development. Demonstrated determinants social impact of their use. Principles of economic evaluation using recreational resources. The necessity of an ideology that would take into account current trends in the transition to a liberal market economy and entry into international structures. The fate of civilization depends not only on man's relationship to nature, but also from the continuity of generations in understanding their needs, both material and spiritual, to preserve human, civilization values and traditions of humanism. Of particular importance is the evaluation of the effectiveness and use of recreational resources, which should combine not only economic and social components, but also include an assessment of measures for the protection and restoration of such resources. Economic feasibility and validity term use of a recreational resource embodied through the level of profitability from its use for tourism purposes. However, in the context of sustainable development, the economic effect is adjusted based on the level of expenditure on maintenance of recreational resources in good condition and it plays that affects the increase in value terms of resource and hardly contributes to the current level of profitability from its use.